Antimicrobial activity and mechanisms of action of Origanum vulgare L. essential oil: effects on membrane-associated properties - Armenuhi Moghrovyan; Naira Sahakyan (AIMS Biophysics)
Historically, essential oils (Eos) have been applied in diverse ways, with modern science confirming their antimicrobial, antioxidant, anti-inflammatory, and neuroprotective properties. Origanum vulgare (oregano) is a notable source of EOs, being particularly rich in compounds like thymol, carvacrol, and β-caryophyllene, which contribute to its potent antibacterial effects. These include disruption of bacterial cell membranes, interference with quorum sensing, and inhibition of biofilm formation. Oregano EO has shown effectiveness against both antibiotic-resistant and non-resistant bacterial strains, such as Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa. The components of this EO disrupt membrane integrity, ion transport, membrane surface charge, biofilm formation, and other biophysical parameters, eventually leading to cell death. Research highlights its potential in combatting antibiotic resistance, either alone or in synergy with traditional antibiotics. Additionally, oregano EO holds promise as a natural therapeutic agent. Continued study of its complex chemical interactions will further elucidate its full potential in antimicrobial therapy. This review article presents the possible mechanisms of the antimicrobial action of oregano essential oil and its application prospects.